STUDYING THE FACTORS AFFECTING PROTECTED AGRICULTURE FARMERS' ADOPTION OF PALESTINIAN GOOD AGRICULTURAL PRACTICES (PAL-GAP) IN THE NORTHERN WEST BANK - Al-Masri, Haneen (An-Najah National University, 2025)
Agriculture in Palestine is considered an essential part and component of Palestinian national, cultural, economic and social life. The agricultural sector contributes to creating job opportunities, increasing income and achieving food security for many Palestinian families.The security and safety of locally traded food is one of the most important issues of concern to all parties and participants in the value chain of various agricultural production.The necessity of adopting modern specialized programs locally and internationally to ensure the safety and security of agricultural and food products from any chemical residues. The necessity of obtaining a high level of quality for agricultural and food products and producing them in an environmentally friendly manner, in response to consumer demand and their right to obtain a safe product. This study aims to examine the factors affecting the adoption of Palestinian good agricultural practices by farmers (Pal Gap) in Tulkarm, Jenin and Nablus governorates. The Palestinian government seeks to direct agricultural production systems towards sustainable and environmentally safe agriculture to contribute to improving farmer income. Direct Palestinian farmers to produce healthy and safe crops and link them to new markets by achieving the Palestinian strategic objectives of good agricultural practices. Adopting economically viable good agricultural practices enhances the reduction of agricultural chemical inputs locally and develops good agricultural practices while ensuring the implementation of a complete and comprehensive crop system from farmer to consumer. A random sample of 291 irrigated vegetable farmers from three northern governorates was selected to complete the questionnaire study tool. The first part of the questionnaire included demographic and farm-related variables such as location, gender, age, marital status, number of family members, educational level, economic status, source of family support, nature of farm work, family income, number of individuals working on the farm, type of agricultural holding, farm area, and participation in community institutions. The second part consisted of questions related to farmers' awareness, interest, and evaluation of Good Agricultural Practices (GAP) and the actual practices implemented by vegetable growers on their farms. This section aimed to assess the extent to which farmers adopt Palestinian Good Agricultural Practices (PAL-GAP), whether they hold a PAL-GAP certificate or are interested in obtaining one, and to identify the obstacles and challenges that hinder adoption. The results indicated that 10% of the sampled farmers hold a Pal Gap certificate. While the majority implement some Good Agricultural Practices (GAP), many expressed a willingness to adopt the full set of Palestinian Good Agricultural Practices; however, they lack the financial resources necessary for implementation. The results showed that farmers’ awareness of Good Agricultural Practices (GAP) was high, averaging 71%. Similarly, farmers’ interest in and evaluation of GAP was also high. However, farmers' actual implementation of GAP was found to be at a moderate level. These findings suggest the need to enhance farmers' understanding of the PAL-GAP concept through awareness workshops explaining the certification requirements. In addition, hands-on training should be provided on the practical aspects of implementing GAP, emphasizing worker welfare and safety. Financial support is also essential to encourage farmers to pursue PAL-GAP certification. This would facilitate the marketing of their products, increase farmers’ profitability, and ensure consumer access to safe and healthy agricultural produce. Furthermore, the establishment of high-quality packaging centers would improve product quality, enhance shelf life, and help open export opportunities for Palestinian agricultural products.
دراسة العوامل المؤثرة على تبني مزارعي الزراعة المحمية للممارسات الزراعية الجيدة الفلسطينية (PAL-GAP) في شمال الضفة الغربية